2017
DOI: 10.1007/s00421-017-3749-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local heating and cooling on skeletal muscle transcriptional response related to myogenesis and proteolysis

Abstract: These results suggest an impaired muscle growth response with local cold application compared to local heat application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
2
14
1
2
Order By: Relevance
“…signalling proteins that regulate protein translation-initiation (i.e. This is in line with a recent study showing that prolonged muscle cooling around resistance exercise does not change the gene expression of these markers of muscle protein breakdown compared to muscle heating (Zak et al 2018). Therefore, these findings with respect to anabolic signalling could not explain the differences we found in myofibrillar protein synthesis between the CWI and CON leg.…”
Section: Discussionsupporting
confidence: 87%
“…signalling proteins that regulate protein translation-initiation (i.e. This is in line with a recent study showing that prolonged muscle cooling around resistance exercise does not change the gene expression of these markers of muscle protein breakdown compared to muscle heating (Zak et al 2018). Therefore, these findings with respect to anabolic signalling could not explain the differences we found in myofibrillar protein synthesis between the CWI and CON leg.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with a recent study showing that prolonged muscle cooling around resistance exercise does not change the gene expression of these markers of muscle protein breakdown compared to muscle heating (Zak et al . ). In addition, it was recently shown that there were no clear effects of postexercise CWI on markers of muscle protein breakdown both before and after 7 weeks of resistance‐type exercise training (Fyfe et al .…”
Section: Discussionmentioning
confidence: 97%
“…The gene expression of the IGF-1 isoforms IGF-1Ea, IGF-1Eb, and IGF-1Ec (also known as mechano growth factor) and the IGF-1 receptor increases acutely in skeletal muscle after resistance exercise (Psilander et al, 2003;McKay et al, 2008;Wilborn et al, 2009;Heinemeier et al, 2013). Among the negative regulators of muscle growth, muscle-specific RING finger (MuRF)-1 mRNA increases acutely (Louis et al, 2007;Drummond et al, 2008;Mascher et al, 2008;Reitelseder et al, 2014;Stefanetti et al, 2014;Zak et al, 2018), as does the expression of genes encoding various proteins in the ubiquitin−proteasome pathway (Mahoney et al, 2008). By contrast, myostatin expression decreases (Louis et al, 2007;Deldicque et al, 2008;Drummond et al, 2008;Mascher et al, 2008;Wilborn et al, 2009;Zak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the negative regulators of muscle growth, muscle-specific RING finger (MuRF)-1 mRNA increases acutely (Louis et al, 2007;Drummond et al, 2008;Mascher et al, 2008;Reitelseder et al, 2014;Stefanetti et al, 2014;Zak et al, 2018), as does the expression of genes encoding various proteins in the ubiquitin−proteasome pathway (Mahoney et al, 2008). By contrast, myostatin expression decreases (Louis et al, 2007;Deldicque et al, 2008;Drummond et al, 2008;Mascher et al, 2008;Wilborn et al, 2009;Zak et al, 2018). Acute changes in the expression of atrogin-1 (also known as muscle atrophy F-box or F-box protein 32) (Louis et al, 2007;Deldicque et al, 2008;Mascher et al, 2008;Manini et al, 2011;Nader et al, 2014;Reitelseder et al, 2014;Stefanetti et al, 2014;Zak et al, 2018) and FoxO (Louis et al, 2007;Manini et al, 2011;Reitelseder et al, 2014;Stefanetti et al, 2014;Zak et al, 2018;Fyfe et al, 2019;Fuchs et al, 2020) in skeletal muscle after resistance exercise are more variable and time-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation